A Stoichiometric Approach to Quantitative Structure−Property Relationships (QSPR) - Fishtik, Ilie; Datta, Ravindra (Journal of Chemical Information and Computer Sciences, 2003)
An unusual analogy between the quantitative structure−property relationships (QSPR), stoichiometry, chemical thermodynamics, and kinetics is presented. Namely, the conventional ordinary least-squares (OLS) QSPR analysis is modified so as to explicitly minimize the residuals of the species subject to a set of linear relations among the residuals. The ways the linear relations among the residuals are visualized and defined totally resemble the formalism of chemical stoichiometry and, therefore, were called isostructural reactions. It is further proved that the residuals may be uniquely partitioned into a sum of contributions associated with a set of isostructural reactions that have the same properties as the response reactions (RERs) previously deduced by us from chemical thermodynamics and kinetics. This finding is shown to be a useful tool for a deeper understanding of the QSPR. In particular, the isostructural RERs approach may be effectively used to detect the outliers.